Parents regulate arousal while sharing experiences with their child: a study of pupil diameter change responses - Jessica Yarmolovsky; Maya Sabag; Maya Sabag; Or Lipschits; Or Lipschits; Ronny Geva; Ronny Geva (Frontiers in Human Neuroscience, 2023)
IntroductionParents provide their children with their first exposures to reciprocal shared experiences, and parental modeling of socio-emotional behaviors and regulatory responses largely influences their child’s behavioral and neurological development. Some parental reactions are conscious, while others are non-volitional. This project aimed to explore parent-child pupil dilation change responses during shared interactions, specifically, whether parents’ neuro-regulatory responses when sharing experiences with their child are different than responses of children interacting with their parents or children and adult peers sharing with each other.MethodsTo test this, four distinct interacting groups were recruited: (1) Parents sharing with their child; (2) Children sharing with their parent; (3) Children sharing with peers; and (4) Adults sharing with peers. All dyads engaged in a computerized shared imagery task, which facilitates communication and mental imagery during a shared experience. During the task, pupil diameter change was recorded as a measure of regulatory response.ResultsFindings highlight that parents sharing with their child have lower pupil diameter change than children sharing with their parents (p < 0.01), children sharing with peers (p < 0.01), and adults sharing with peers (p < 0.05), While no differences were seen between children sharing with parents, children sharing with peers or adults sharing with peers.DiscussionFindings deepen the understanding of the neuroscience of parenting, by suggesting that parents, even of older children and adolescents, tend to regulate their arousal when interacting with their child, a response that proves to be unique compared to other dyad types for sharing experiences. Considering this dynamic, findings may direct future parent-led intervention methods to improve the child’s socio-emotional development.